Tri‐trophic ecology of native parasitic nest flies of birds in Tobago. Issue 1 (27th January 2017) - Knutie, Sarah A.; Herman, Jordan M.; Owen, Jeb P.; Clayton, Dale H.
Abstract: Introduced parasites threaten host populations around the world. For example, introduced parasitic nest flies ( Philornis downsi ) have contributed to the decline of several species of Darwin's finches in the Galápagos Islands. Introduced parasites are thought to have severe effects on native hosts because the hosts do not have effective defenses against such parasites and/or because introduced parasites have escaped the native enemies that keep their own populations in check. Studying effects of parasites on native hosts is an essential step in testing these causal hypotheses. We conducted a field experiment to assess the virulence of a native species of Philornis ( Philornis trinitensis ), which parasitizes birds on the island of Tobago. We manipulated flies in nests of black‐faced grassquits ( Tiaris bicolor ), a close relative of Darwin's finches, as well as tropical mockingbirds ( Mimus gilvus ), a congener of the Galápagos mockingbird ( Mimus parvulus ). We predicted that P. trinitensis would be relatively avirulent because its native hosts in Tobago have had time to evolve effective defenses against it. We also noted the presence of parasitoids and other enemies of Philornis in Tobago nests. Surprisingly, effects of native P. trinitensis on Tobago birds were similar to the effects of introduced P. downsi on birds in the Galápagos. Flies reduced the reproductive success of grassquits, but not mockingbirds, which are also relatively unaffected by Philornis in the Galapagos. Thus, native Philornis flies are not less virulent than introduced flies. The prevalence of Philornis in Tobago was lower than the prevalence of Philornis in the Galápagos. Presumed enemies of Philornis (parasitoid wasps and ants) were relatively common in nests of birds in Tobago, but largely absent from nests in the Galápagos. We suggest that introduced P. downsi in the Galápagos is widespread, not because hosts lack defenses, but because it has left its enemies behind.